PERBANDINGAN DAYA GUNA AUTO KO-INDUKSI PROPOFOL 0,25 MG/KGBB DENGAN 0,5 MG/KGBB DALAM MENGURANGI DOSIS INDUKSI PROPOFOL PADA OPERASI ELEKTIF DENGAN ANESTESI UMUM - , NOVA KRISDIYANTORO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : propofol when used as the sole induction causes a decrease in arterial blood pressure and cardiac output were significant, rapid intravenous administration resulted in a temporary stop breathing due to depression of ventilation. To get the minimal side effects and cost effective, it is necessary to auto co-induction. Objective : this study was aimed to know that the power to auto co-induction of propofol 0.25 mg/kg intravenously with propofol auto-co-induction 0.5 mg/kg intravenously induction dose of propofol in reducing the elective surgery with general anesthesia. Method : the used method was a double-blind randomized controlled trial (RCT). The subjects were 90 patients and divided in two groups, which were group A is a group that gets auto propofol co-induction of 0.25 mg/bw intravenously and group B is group that get auto co-induction of propofol 0.5 mg/bw intravenously were included in the inclusion criteria. Measurements performed on patient demographics: age, sex, weight, height, BMI (Body Mass Index), physical status (ASA) and the initial hemodynamic (systolic blood pressure, diastolic blood pressure, mean arterial blood pressure and pulse heart). The next recording is an induction dose of propofol, after induction and hemodynamic side effects occur. The data ware analyzed using independent t-test and chi-square (p<0.05). Result : there was a significant difference in the matter of induction dosage which needed on both groups, which as much as 16,13 mg (p=0,001) whilst in Group A (119,5911 ± 12,24973) and Group B (135,7222 ± 12,93408), so as 0,25 mg/bw propofol auto co-induction administration had more potency with 0,5 mg/bw dosage in order to decreasing propofol induction dosage. IoC mark which resulted after one minute of coinduction auto dosage had showed (81,69 ± 2,26) in Group A and (80,84 ± 1,99) for Group B whereas these results implified the non significant difference (p=0,063). Hemodynamic changes measured before the auto co-induction and after the induction of propofol on both groups still within in safe boundaries and had not showed the significant difference (p>0,05). Conclusion : auto co induction with propofol 0,25mg/bw intravenously has a better potency than propofol 0,5 mg/bw intravenously in order to reduce the propofol total induction dosage in elective surgeries with general anesthesia and its propofol differential dosage need of 16,13 mg (p = 0,001).